Analisis Penerapan Biaya Standar Sebagai Alat Pengendalian Biaya Produksi Pada (Studi Pt.Bibit Alam Sampoerna Kediri) - Imam Mustofa; Nur Ainiyah; Hari Setiono; Hartono Hartono (Universitas Katolik Widya Karya Malang, 2023)
This study aims to determine the application of standard costs, raw material costs, labor costs, and overhead costs at PT.Bibit Alam Sampoerna. The object of this study is the financial statements of the company administration for every transaction that comes out and costs, PT.Bibit Alam Sampoerna is a company engaged in Freshwater lobster cultivating services. The tools used in this research are interviews used as a data collection technique if the researcher wants to conduct preliminary studies to find problems that must be investigated or want to know things from respondents who are more in-depth and in a slightly small number of respondents. And observation is the most basic way to obtain information about social phenomena through the process of observation. Direct observation regarding the work environment and production processes from raw materials to finished product processes. The analysis technique used in this research is descriptive quantitative. Researchers will analyze the data in the form of costs in the production activities of PT. Seed Alam Sampoerna regarding the cost of production. Collecting Data, Identifying Company Standard Costs, Separating these costs based on cost behavior, namely variable costs incurred in the production process, Analysis of raw material costs, Analysis of labor costs, Analysis of factory overhead costs, Calculating the cost of production using the calculation according to researcher. After the company determines the standard cost of production costs, the company can carry out its production activities in accordance with its production goals. The standard cost set is a guideline or measure for each production cost that will be incurred. Research results To increase the effectiveness of production cost control, companies must implement a standard cost system which is used as a guideline for production costs.